Ewolucja samorządu terytorialnego w Polsce w latach 1989-1998 - Teclaw, Dominika (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In the present article focuses on showing the transformation of local government in Poland after 1989. The writing discussed the issues related to the evolution of local government on the ground in the context of the changing political and social reality. Shown are the determinants of the transformation of local government, were also presented new legal conditions and their impact on the evolution of the local administration. Particular attention was paid to the reform of the administration in 1998 and its impact on the shape of the current administration.